Summa Theologica, Part I (Prima Pars) : From the Complete American Edition - Thomas, Aquinas, Saint, 1225?-1274 (Salt Lake City, UT : Project Gutenberg, 2006)
"Summa Theologica, Part I (Prima Pars)" by Saint Thomas Aquinas is a theological work written in the 13th century. This monumental compendium presents the main theological teachings of the Catholic Church, designed as an instructional guide for beginning theology students. Through a structured question-and-answer format, Aquinas explores fundamental topics including the existence and nature of God, Creation, angels, and humanity. Drawing from Christian, Islamic, Jewish, and ancient philosophical sources, this unfinished masterpiece systematically builds arguments for Christian theology, establishing itself as one of history's most influential philosophical and theological texts. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Summa_Theologica
Release date is 2006-01-26
Produced by Sandra K. Perry, with corrections and supplementation by David McClamrock
Keywords: Theology, Doctrinal -- Early works to 1800; Catholic Church -- Doctrines -- Early works to 1800; God -- Omnipresence -- Early works to 1800; God -- Attributes -- Early works to 1800